Responding to growing European Union-skepticism? The stances of political parties toward European integration in Western and Eastern Europe following the financial crisis. (March 2016) - Rohrschneider, Robert; Whitefield, Stephen
Using data from two expert surveys conducted in 2007–2008 and 2013 in 24 European democracies, we examine the response of political parties—especially mainstream ones—across the European Union to the growth in public European Union-skepticism since the onset of the financial crisis. Theoretically, we point to competing spatial and reputational pressures on mainstream and extreme parties to adjust their integration positions. We find that mainstream parties respond fairly little over time and that this has left a representational opening for extreme parties, which is especially filled by new European Union-skeptic parties.